Replacement of dietary soy- with air classified faba bean protein concentrate alters the hepatic transcriptome in Atlantic salmon (Salmo salar) parr - De Santis, Christian; Crampton, Viv; Bicskei, Beatrix; Tocher, Douglas R (Comparative Biochemistry and Physiology Part D: Genomics and Proteomics, 2015)
The production of carnivorous fish such as Atlantic salmon (Salmo salar) is dependent on the availability of high quality proteins for feed formulations. For a number of nutritional, strategic and economic reasons, the use of plant proteins has steadily increased over the years, however a major limitation is associated with the presence of anti-nutritional factors and the nutritional profile of the protein concentrate. Investigating novel raw materials involves understanding the physiological consequences associated with the dietary inclusion of protein concetrates. The primary aim of the present study was to assess the metabolic response of salmon to increasing inclusion of air-classified faba bean protein concentrate (BPC) in feeds as a replacement for soy protein concentrate (SPC). Specifically, we tested treatments with identical contents of fishmeal (222.4 g kg-1) and progressively higher inclusion of BPC (0 g kg-1, 111.8 g kg-1, 223.6 g kg-1, 335.4 g kg-1, 447.2 g kg-1) substituting SPC. This study demonstrated a dose-dependent metabolic response to a plant ingredient and was the first to compare the nutrigenomic transcriptional responses after substitution of terrestrial feed ingredients such as BPC and SPC without withdrawal of marine ingredients. It was found that after eight weeks a major physiological response in liver was only evident above 335.4 g kg-1 BPC and included decreased expression of metabolic pathways, and increased expression of genes regulating transcription and translation processes and the innate immune response. Furthermore, we showed that the nutritional stress caused by BPC resembled, at least at hepatic transcriptional level, that caused by soybean meal (included as a positive control in our experimental design). The outcomes of the present study suggested that Atlantic salmon parr might efficiently utilize moderate substitution of dietary SPC with BPC, with the optimum inclusion level being around 120 g kg-1in the type of feeds tested here.